2019
DOI: 10.1590/1518-8345.2853.3072
|View full text |Cite
|
Sign up to set email alerts
|

Identification of warning signs for prevention of in-hospital cardiorespiratory arrest

Abstract: Objective:to identify the occurrence of warning signs and changes in vital signs in individuals who experienced in-hospital cardiorespiratory arrest and correlate them with the occurrence of this event. Method:this is a retrospective, analytical and quantitative study that included 218 medical records of patients who suffered in-hospital cardiorespiratory arrest and identified warning signs and alterations in vital signs. Mean, standard deviation, median, minimum and maximum values were calculated for the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
0
9
0
8
Order By: Relevance
“…O grupo de risco o qual se destaca a parada cardíaca são as pessoas com disfunções cardíacas, doenças pulmonares crônicas, tabagistas, diabéticos, obesos, indivíduos com taxas de colesterol elevadas, com alta taxa de triglicerídeos e pessoas que não possuem hábitos saudáveis de vida e uma alimentação balanceada (SOUZA et al, 2019).…”
Section: Objetivosunclassified
“…O grupo de risco o qual se destaca a parada cardíaca são as pessoas com disfunções cardíacas, doenças pulmonares crônicas, tabagistas, diabéticos, obesos, indivíduos com taxas de colesterol elevadas, com alta taxa de triglicerídeos e pessoas que não possuem hábitos saudáveis de vida e uma alimentação balanceada (SOUZA et al, 2019).…”
Section: Objetivosunclassified
“…Early warning tools to help identify patients at the highest risk of death could help countries like Ghana with resource allocation and clinical decision making (Figure 1). Multiple studies have shown that critical illness and serious adverse events in hospitalized patients are preceded by signs of clinical deterioration in up to 80% of those affected [5][6][7][8]. Therefore, changes in physiological parameters can be used to predict adverse events such as shock, cardiac arrest, death, and unplanned intensive care unit (ICU) admissions [9].…”
Section: Introductionmentioning
confidence: 99%
“…A parada cardiorrespiratória (PCR) pode ser definida como a interrupção súbita dos batimentos cardíacos, movimentos respiratórios e perda imediata da consciência, podendo acarretar lesão cerebral irreversível e morte. É uma condição clínica emergencial com alto índice de gravidade, caracterizada pela falha da função respiratória, confirmada pela ausência de sinais de circulação (SOUZA et al, 2019).…”
Section: Introductionunclassified
“…Anualmente, mais de 200 mil adultos sofrem PCR em ambiente intra-hospitalar nos Estados Unidos, estima-se que a maioria desses eventos poderiam ser evitados pela identificação de sinais prévios e a instauração de terapêutica adequada (SOUZA et al, 2019).…”
Section: Introductionunclassified